Antidepressant Effects of Mitragyna Speciosa Korth Extract on Diabetic Rats - Putra, Reza Hery Mahendra; Awwaliyah, Evi Sylvia; Salim, Hotimah Masdan; Alam, Ilham Putera; Rofiq, Ainul (UNUSA Press, 2024)
Background: Diabetes mellitus is most common associated with neurological complications, including depressive symptoms, so this study investigated whether mitragyna may provide benefits in reducing depressive symptoms in animal models of diabetes. This study aims to evaluate the effect of mitragyna as a potential antidepressant agent in animal models of diabetes mellitus using the Force Swimming Test (FST). Methods: In this study, diabetes mellitus rats were induced by administering streptozotocin and then divided into four groups: control group (Control), Group Diabetes (DM), Mitragyna treatment group (DM+EMS 15mg) and (DM+EMS 30mg). After the treatment period, the rats were then tested with the FST, which is used to measure immobility behavior which can be used as an indicator of depressive symptoms. Results: The results showed that the treatment group that received mitragyna showed shorter immobility times compared to the control group (P<0.01), indicating an increased active response in facing FST stressors. Conclusion: These results indicate that mitragyna has potential as an antidepressant agent in reducing depressive symptoms in rats models of diabetes mellitus.